Analisis Kontribusi Pelatihan, Kompensasi dan Disiplin Kerja terhadap Kinerja Pegawai Studi pada SMK Negeri 1 Peusangan Kabupaten Bireuen - Yusuf, M. (Singkite Journal, 2023)
This study aims to analyze the contribution of employee training, compensation and motivation factors to employee performance. By using the quantitative type associative method. The problem analysis method uses the path analysis model. Based on data collected through questionnaires to 99 employees at SMK Negeri 1 Peusangan, Bireuen Regency. The results showed that: (1) there was a direct and indirect effect of training on employee performance of 28.72%, (2) there was a direct and indirect effect of compensation on employee performance of 25.02%, (3) there was a direct effect of and indirect compensation for employee performance, indirect work discipline for employee performance of 30.1%. (4). Simultaneously employee training, compensation and work discipline make a positive contribution of 40.9% to employee performance